1988
DOI: 10.1177/036354658801600606
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of anterior cruciate ligament with carbon fiber

Abstract: During a follow-up period of 16 weeks in 18 pigs, macroscopical and histological studies revealed invasion of fibroblasts and mesenchymal cells around the carbon fiber prosthesis inserted to replace the ACL but scarce tissue ingrowth into the prosthesis proper. There was no adherence of the carbon ligament onto the bony channels. The peak tensile strength of the reconstructed ligament was about one third of the paired normal ACL ligament during the 16 week experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…However, most studies (Mäkisalo et al 1988, Rodeo et al 1993) have been done on animals (dog, pig, sheep and rabbit).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most studies (Mäkisalo et al 1988, Rodeo et al 1993) have been done on animals (dog, pig, sheep and rabbit).…”
Section: Discussionmentioning
confidence: 99%
“…If bone growth had taken place in the tendon to the same extent as in the two studies mentioned, the BMD would have increased in the center of the tunnel. Mäkisalo et al (1988) reported that all carbon ber prostheses enveloped in fascia lata failed mechanical tests by pulling out the prosthesis of the fascia lata. They found maturing scar tissue in the bone tunnel between the viable fascia and the bone.…”
Section: Discussionmentioning
confidence: 99%
“…Rushton et al (197) questioned the use of carbon fiber after finscattering of carbon particles and synovitis in operated knees. Carbon fiber is known to be brittle and difficult to handle, stiffness causes early breakage at any point of flexion at sharp angle and functional ingrowth has not been demonstrated (198,199).…”
Section: Synthetic Ligaments and Allograftsmentioning
confidence: 99%
“…Unfortunately, a high rate of complications was associated with the use of these synthetic substitutes, making their use not widely accepted. 8 , 9 …”
mentioning
confidence: 99%